2011
DOI: 10.1109/tbme.2010.2098031
|View full text |Cite
|
Sign up to set email alerts
|

In-Plane Biocompatible Microfluidic Interconnects for Implantable Microsystems

Abstract: Small mammals, particularly mice, are very useful animal models for biomedical research. Extremely small anatomical dimensions, however, make design of implantable microsystems quite challenging. A method for coupling external fluidic systems to microfluidic channels via in-plane interconnects is presented. Capillary tubing is inserted into channels etched in the surface of a Si wafer with a seal created by Parylene-C deposition. Prediction of Parylene-C deposition into tapered channels based on Knudsen diffus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 18 publications
0
17
0
Order By: Relevance
“…Translationally, it may be that ALD combined with other critical compounds could be given systemically (orally, time-release skin patch), if there are no side effects, or have beneficial systemic effects for an aging mammal. Alternatively, if side effects are detrimental (which was not the case in the current study, e.g., stable blood pressure throughout the treatment period), a medicine to improve hearing in the elderly could be given locally to the inner ear via microsystem delivery techniques that we are currently developing [ 79 - 82 ], or via transtympanic injections into the middle ear near the round window, perhaps using nanoparticles as drug carrying vehicles.…”
Section: Discussionmentioning
confidence: 99%
“…Translationally, it may be that ALD combined with other critical compounds could be given systemically (orally, time-release skin patch), if there are no side effects, or have beneficial systemic effects for an aging mammal. Alternatively, if side effects are detrimental (which was not the case in the current study, e.g., stable blood pressure throughout the treatment period), a medicine to improve hearing in the elderly could be given locally to the inner ear via microsystem delivery techniques that we are currently developing [ 79 - 82 ], or via transtympanic injections into the middle ear near the round window, perhaps using nanoparticles as drug carrying vehicles.…”
Section: Discussionmentioning
confidence: 99%
“…Johnson et al demonstrated that interfaces between polyimide tubings and silicon/glass chips sealed by Parylene C can withstand pressures as high as 827 kPa (Fig. 12c) [194]. More recently, a novel macro-to-micro interfacing technique was developed by our group (Fig.…”
Section: Permanent Fluidic Connectionsmentioning
confidence: 99%
“…For example, tubings can be connected to (a) a tape covering a paper-based microfluidic, (b) a silicon chip by means of soldering, (c) a LOC device using in-plane insertion of tubings followed by conformal deposition of Parylene C, and (d) a microfluidic chip with mechanical interlocking of tapered tubings. (a) After [137], (b) after [192], and (c) after [194]. structures.…”
Section: Electrical Connectionsmentioning
confidence: 99%
“…Microfluidic interconnects to polyimide microcapillary tubing were created as described in [ 37 ]. Briefly, a 0.17 mm cover glass (18 mm × 18 mm) was adhered to the chip along the interconnect edge to prevent resin from flowing into the microchannels during the direct write step and to provide a clean opening for the insertion of the capillary tubing.…”
Section: Fabricationmentioning
confidence: 99%